COVID-19 Pandemic in Brunei Darussalam - Wei Shan Ang; Jodi Woan-Fei Law; Vengadesh Letchumanan; Yong Sze Ong; Yatinesh Kumari; Long Chiau Ming; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Within ASEAN, Brunei is one of the low population density nations successfully combating the first wave of the COVID-19 pandemic in 2020. As of 4th January 2023, over 2.6 hundred thousand confirmed cases of COVID-19, with 225 deaths, had been reported in Brunei. This paper outlines the COVID-19 trends in Brunei and strategies taken by the health authorities to contain the pandemic. Three waves of COVID-19 have hit Brunei, with the first case of COVID-19 reported on 9th March 2020. The adoption of the “whole of nation approach” has proven to be effective in managing the outbreak. Early and decisive interventions taken by authorities and the public’s cooperation have been a remarkable success story. The key success factors are effective pandemic containment measures, public communication strategy, and enhanced surveillance mechanisms supported by the mass testing program and contact tracing. A national vaccination strategy ensuring adequate vaccine distribution and effective administration has been rolled out to render lasting protection against the infection. National COVID-19 Recovery Plan Framework and a gradual COVID-19 de-escalation plan were implemented to ensure a smoother transition to the new normal. This review provides valuable insights into the development of a robust pandemic leadership model and highlights the lessons and strategies that other countries can adopt for any future uncertainties.